(untitled) (International Journal of Engineering and Computer Science, 2016)
The Nqueen problem is to place N queens on an NxN chessboard such that no two queens attack each other. Traditionally, algorithm has been written for serial computation recent advances in software and hardware allow parallelism. This paper investigate the possibility of finding the solutions of Nqueen problem by recently introduced Rakhya’ method modified to run on parallel system.